2020
DOI: 10.1186/s13063-020-04774-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of antiviral combination therapy in symptomatic patients of Covid-19 infection - a randomised controlled trial (SEV-COVID Trial): A structured summary of a study protocol for a randomized controlled trial

Abstract: Objectives 1. To compare the safety and efficacy of Hydroxychloroquine with Ribavirin and standard treatment in patients with non-severe COVID-19 infection 2. To compare the safety and efficacy of standard treatment, Lopinavir-ritonavir with Ribavarin, and Hydroxychloroquine with Ribavirin in patients with severe COVID-19 infection Trial design The study is an Open label, Parallel arm design, stratified randomised controlled trial. Patients will be categorised as non-severe or severe based on predefined crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It was reported that for influenza patients with high viral load at the beginning of disease symptoms, combinational antiviral therapy is more effective than monotherapies ( 46, 47 ). This is mirrored during the initial phase of the COVID-19 pandemic, where multiple combinational therapeutic approaches using several repurposed drugs show mild to moderate efficacy in treating severely ill patients ( 48-50 ). To extend this combinational therapeutic approach to treat COVID-19 patients in vitro , we tested combination treatment of SF2523 and remdesivir as described above.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that for influenza patients with high viral load at the beginning of disease symptoms, combinational antiviral therapy is more effective than monotherapies ( 46, 47 ). This is mirrored during the initial phase of the COVID-19 pandemic, where multiple combinational therapeutic approaches using several repurposed drugs show mild to moderate efficacy in treating severely ill patients ( 48-50 ). To extend this combinational therapeutic approach to treat COVID-19 patients in vitro , we tested combination treatment of SF2523 and remdesivir as described above.…”
Section: Discussionmentioning
confidence: 99%
“…PCR and Real-Time PCR PCR and RT-PCR are considered important molecular biology techniques, first introduced in the 1980s. The techniques are based on the amplification and detection of a particular gene (Panawala, 2017). The amplification of genetic material is beneficial for obtaining the satisfying quantity of specimens required for a laboratory study.…”
Section: Nucleic Acid Amplification Testsmentioning
confidence: 99%
“…Both PCR and RT-PCR involve the utilization of certain enzymes. PCR uses a DNA template, whereas RT-PCR uses RNA (Panawala, 2017). Several RT-PCR-based test kits have also been developed .…”
Section: Nucleic Acid Amplification Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its combination with other antivirals is being tried in the SEV trial, the result of which is yet to be published. [68]…”
Section: Ribavirinmentioning
confidence: 99%